2011
DOI: 10.1002/eji.201141855
|View full text |Cite
|
Sign up to set email alerts
|

A new synthetic TLR4 agonist, GLA, allows dendritic cells targeted with antigen to elicit Th1 T‐cell immunity in vivo

Abstract: SUMMARY Protein-based vaccines offer safety and cost advantages but require adjuvants to induce immunity. Glucopyranosyl Lipid A (GLA) is a new synthetic non-toxic analogue of lipopolysaccharide. In mice, in comparison to non-formulated LPS and another analog Monophosphoryl Lipid A, formulated GLA induced higher antibody titers and generated Type 1 T cell responses to HIV gag-p24 protein in spleen and lymph nodes, which was dependent on TLR4 expression. Immunization was greatly improved by targeting HIV gag p2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 60 publications
2
59
0
Order By: Relevance
“…It was recently reported that depletion of CD11c ϩ cells had no effect on antibody responses but impaired T-cell immunity after targeting antigen to DEC-205 for immunization. 36 Furthermore, germinal center B cells in mouse spleen express high level of DEC-205. 22 The effect of antigen targeting to DEC-205 on humoral immune response needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently reported that depletion of CD11c ϩ cells had no effect on antibody responses but impaired T-cell immunity after targeting antigen to DEC-205 for immunization. 36 Furthermore, germinal center B cells in mouse spleen express high level of DEC-205. 22 The effect of antigen targeting to DEC-205 on humoral immune response needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Research with a new synthetic TLR4 agonist, glucosyl pyranosyl lipid A (GLA), is also underway by Longhi together with Steve Reed from Seattle (129). Different classes of adjuvants might be needed to tailor the immune response to the particular pathogen and to optimize protective immunity.…”
Section: Wwwannualreviewsorg • Decisions On Dendritic Cellsmentioning
confidence: 99%
“…DC-SIGN has also been shown to recognize SIgA which may present a novel targeting strategy [245]. Targeting of DCs can also be coupled to the delivery of TLR ligands as adjuvants which potently enhanced the ability of this approach to enhance Th1-mediated responses following subcutaneous vaccination [246].…”
Section: Targeted Delivery To Specific Tissues and Cellsmentioning
confidence: 99%